2001
DOI: 10.1007/s002610000168
|View full text |Cite
|
Sign up to set email alerts
|

Virtual cystoscopy of the bladder based on CT and MRI data

Abstract: Carcinoma of the bladder can be a serious and complex condition that is not always easy to diagnose with radiologic methods. Numerous investigations are available to establish the diagnosis and demonstrate extravesical manifestations. This article updates the role of virtual cystoscopy based on computed tomographic (CT) data at different dose levels and magnetic resonance imaging (MRI) data in the diagnosis of the carcinoma of the bladder. The appearances of normal bladder and polypoid bladder carcinoma are sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 20 publications
0
33
0
3
Order By: Relevance
“…It has drawbacks, however, such as invasiveness, discomfort to the patient, high costs, iatrogenic injury, and urinary sepsis. [1][2][3][4][5][6][7][8][9] Because some lesions, such as those of bladder cancer, usually recur, necessitating long-term follow-up, an accurate imaging method would help to reduce the number of CC procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has drawbacks, however, such as invasiveness, discomfort to the patient, high costs, iatrogenic injury, and urinary sepsis. [1][2][3][4][5][6][7][8][9] Because some lesions, such as those of bladder cancer, usually recur, necessitating long-term follow-up, an accurate imaging method would help to reduce the number of CC procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual cystoscopy (VC) has been applied recently to study bladder tumors. [1][2][3][4][5][6][7][8][9] It consists of three-dimensional (3-D) computer-rendering techniques with the possibility of interactive intraluminal navigation through the bladder simulating conventional cystoscopy (CC). CC remains the gold standard for bladder tumor detection and follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…With a sensitivity of 90.7% and a specificity of 94.0% for the combined analysis of VC and MPR, the performance was comparable to the results reported in the literature for CT cystography and MR cystography. Up to now, however, there has been only limited experience with virtual cystoscopy based on MRI [11][12][13][14][15][16]. In previous studies, CT data sets were used more frequently than MR data sets and showed promising results for the detection of bladder tumors larger than 5 mm [17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the technique of MR cystoscopy, several methods are described in the literature: (1) a T1-weighted breathhold sequence after bladder distension via a catheter with gas or contrast medium (analogous to CT cystoscopy) [16], (2) a T2-weighted sequence with air insufflation of the bladder [23] or (3) a T2-weighted sequence without invasive procedures, which is the method we used [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Ureterorenoskopie durchführbar. Analog zur CT-Technik kann die Blase entweder über einen Katheter mit dem MRT-Kontrastmittel Gadolinium (Gd-DTPA) gefüllt werden [4] oder die Fül-lung wird über die Ausscheidung von i.v. verabreichtem Gd-DTPA erreicht [3,20].…”
Section: Rohdatenerfassung Mittels Mrtunclassified